SOFTWARE KIT "iSES REMOTE LAB SDK" FOR REMOTE LABORATORY - LUSTIG, František (Trends in education, 2015)
We present remote experiments now available for touch and mobile devices. Remote experiments are built with new software kit "iSES Remote Lab SDK". We want to provide non-programming users creation of custom remote experiments. "iSES Remote Lab SDK" is independent on measuring apparatus (currently it is suited for ISES kit, measuring apparatus with COM or USB communication ports, for linear and stepper motors, for certain commercial devices etc.).
Keywords: remote experiments; Physics; HTML5; JavaScript; touch and mobile device.